2016
DOI: 10.1007/s00122-016-2780-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the utility of gene expression and metabolic information for genomic prediction in maize

Abstract: Predictive ability derived from gene expression and metabolic information was evaluated using genomic prediction methods based on datasets from a public maize panel. With the rapid development of high throughput biological technologies, information from gene expression and metabolites has received growing attention in plant genetics and breeding. In this study, we evaluated the utility of gene expression and metabolic information for genomic prediction using data obtained from a maize diversity panel. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
136
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(153 citation statements)
references
References 52 publications
9
136
4
Order By: Relevance
“…85 86 A complementary way in which multiple "omics" can be used is for complex trait prediction, in 87 a similar manner to prediction using genomic data. Different layers of data may provide 88 (partially) non-redundant information about phenotypes (Guo et al 2016). For example, gene 89 expression levels may also capture some environmental effects, i.e., those that affect levels of 90 expression.…”
Section: Introduction 15mentioning
confidence: 99%
See 1 more Smart Citation
“…85 86 A complementary way in which multiple "omics" can be used is for complex trait prediction, in 87 a similar manner to prediction using genomic data. Different layers of data may provide 88 (partially) non-redundant information about phenotypes (Guo et al 2016). For example, gene 89 expression levels may also capture some environmental effects, i.e., those that affect levels of 90 expression.…”
Section: Introduction 15mentioning
confidence: 99%
“…101 However, when the researchers turned to a clinical dataset that included individuals with both 102 DNA and RNA data and tried to predict a quantitative trait, the combined model predicted worse 103 than the best single component model (Wheeler et al 2014). 104 105 Guo et al (2016) used inbred lines of maize with genotype (G), gene expression level (T) and 106 metabolite level (M) information to predict several complex traits using BLUP methodology. In 107 general, MBLUP yielded lower accuracy than all the other models.…”
Section: Introduction 15mentioning
confidence: 99%
“…Values of VIP for Component 1 in the PLS‐DA result were used to filter TGW‐unrelated or low contribution analytes. Predictabilities of TGW for hybrids from the population in 2015 varied from low ( r = 0.47, P = 3.36E‐4) to high ( r = 0.72, P = 8.52E‐10) and then back to low ( r = 0.45, P = 8.14E‐4) with the increasing numbers of metabolic markers, which is similar to results with SNPs, transcripts or metabolites as predictive markers (Guo et al ., ; Slavov et al ., ). At last, after further removing low contribution analytes and additional PLS regression analysis, three hundred was the most appropriate number of analytes to predict grain weight for rice hybrids across environments, which indicated that a certain number of predictive analytes is necessary for high predictability.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, environmental effects should be considered in employing markerbased prediction. In addition, other factors including population structures and numbers of predictive variables also have large effects on predictabilities (Guo et al, 2016;Slavov et al, 2014;Technow et al, 2014;Windhausen et al, 2012;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has seen tremendous advances in genome-scale data analysis, which was possible due to high-throughput DNA sequencing. In this way, single nucleotide polymorphism (SNPs), representing various regions of all chromosomes, are obtained to be applied in genomic studies (Guo et al 2016). …”
Section: Introductionmentioning
confidence: 99%